Posterolateral Corner Reconstruction Using the Anatomical Two-Tailed Graft Technique: Clinical Outcomes in the Multiligament Injured Knee - Woodmass, Jarret M.; Sanders, Thomas L.; Johnson, Nick R.; Wu, Isabella T.; Krych, Aaron J.; Stuart, Michael J.; Levy, Bruce A. (The Journal of Knee Surgery, 2018)
Injury to the posterolateral corner (PLC) of the knee can lead to both varus and rotational instability. Multiple PLC reconstruction techniques have been described, including one-tailed graft (fibula-based constructs) or two-tailed graft (combined fibula- and tibia-based constructs). The purpose of our study was to evaluate the clinical outcomes of anatomical two-tailed graft reconstruction of the PLC in the setting of multiligament knee injuries (MKLIs) with grade III varus instability. Patients were identified through a prospective MLKI database between 2004 and 2013. Patients who received fibular collateral ligament and PLC reconstructions using a two-tailed graft and had a minimum follow-up of 2 years were included. Patients were assessed for clinical laxity grade, range of motion, and functional outcomes using Lysholm and International Knee Documentation Committee (IKDC) scores. Twenty patients (16 male, 4 female) with a mean age of 30.7 (range: 16–52) and a mean follow-up of 52.2 months (range: 24–93 months) were included. Knee dislocation (KD) grades included: 4 KD-1, 10 KD 3-L, 5 KD-4, and 1 KD-5. No patients had isolated PLC injuries. Mean IKDC and Lysholm score were 73.1 ± 25.8 and 78 ± 26, respectively. Mean range of motion was –1.1 to 122.8. In full extension, two patients (10%) had grade 1 laxity to varus stress. In 30 degrees of knee flexion, five (25%) patients had grade 1 laxity, and two (10%) had grade 2 laxity. Anatomical two-tailed PLC reconstruction can reliably restore varus stability when performed on patients with MLKIs and type C posterolateral instability with hyperextension external rotation recurvatum deformity. Satisfactory functional outcome scores were achieved in the majority of patients. This study supports the use of an anatomical two-tailed PLC reconstruction in the multiligament injured knee. The level of evidence is IV, case series.
Keywords: knee; posterolateral corner; knee dislocation